Unraveling Risk Networks of Cultivated Land Protection: An Exploratory Stakeholder-Oriented Case Study in Xiliuhe Town, Hubei Province, China - Zhaoxia Guo (MDPI AG, 2021)
The protection of cultivated land plays an important role in ensuring food security, maintaining social stability, and promoting economic development. The protection of cultivated land involves a range of stakeholders (e.g., governments at different levels, farmers, and land-use organizations) and entails intertwined risk factors (e.g., to economic, environmental, social, and political factors). Therefore, it is crucial to identify and assess key stakeholders and associated risks to better align land protection policies. However, previous studies of risk are fragmented, and there has been little research targeting the complex interactions among risk factors in the protection of cultivated land. Taking Xiliuhe Town as an example, this study analyzes complex and intertwined risk factors from a network perspective in an in-depth case study in a major grain-producing area. The results show that: (1) the risk-factor network of cultivated land protection is relatively sparse, with a total of 142 nodes and 253 links; (2) local governments and land flow-out farmers are the core stakeholders, with strong power and connectivity in the network; (3) taking into account key stakeholders and associated risk factors, a framework for mitigating risks is developed, and a network simulation is performed. Using the simulation results, the effectiveness of the risk-mitigation strategies is assessed and validated. These results shed new light on cultivated land protection and sustainable agricultural development in emerging countries.